Juzgar y resolver las controversias en la Edad Media - Storti, Claudia 1952- (2018)
The period between the 11th and 12th centuries is usually indicated as an age of transition from the early to late Middle Ages. The paper aims at focusing on the continuities and discontinuities in this time, and specifically on how the search for new models and new procedures for the administration of justice played a "constitutional" role, just as it would in many other historical eras to follow. From this perspective, the emergence of positiones in the judicial practices and in the ordines iudiciorum provides an interesting point of view in order to investigate, on one hand, whether the parties were more interested to go to trial or to settle their disputes by negotiations, and, on the other hand, to understand the legal policy of the medieval governments between two conflicting interests: to ensure justice ascertaining the truth and to re-establish peace through arbitration procedures and avoid malicious litigation which might slow down the course of justice.
Il periodo compreso tra XI e XII secolo è normalmente indicato come età di transizione tra alto e basso medioevo. Lo scritto intende mettere a fuoco gli elementi di continuità e di discontinuità di questo periodo soprattu tto con riguardo al fatto che la ricerca di nuovi modelli e di nuove procedure per l'amministrazione della giustizia giocò un ruolo "costituzionale", non diversamente da quanto avvenuto in altri periodi successivi. In questa prospettiva, l'emergere delle positiones nelle prassi giudiziarie e negli ordines iudiciorum offre un interessante punto di vista per verificare, da un lato, se le parti fossero più interessate a andare in giudizio o a risolvere le loro controversie in via negoziale; dall'altro per comprendere la politica giudiziaria degli ordinamenti medievali tra due interessi tendenzialmente contrastanti: quello di assicurare giustizia con l'accertamento della verità e quello di ristabilire la pace sociale tramite arbitrati evitando così con l'abuso del processo il rischio di rallentare la giustizia.